The effect of DAU and PAD to enconomic growth with capital expenditures as intervening variabels - Manggar Wulan Kusuma ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2016)
This study aims to determine whether the general allocation funds and local revenue can affect economic growth in South Sulawesi Province by using variable capital expenditure as an intervening variable. The data source used is secondary data in the form of financial report of local government of regency / city in South Sulawesi Province in 2006 until 2013. Data analysis technique used is Partial Least Square (PLS) analysis. The result of the research shows that 1) General allocation fund has negative effect to capital expenditure; 2) Original revenue of the region has a positive effect on capital expenditure; 3) Capital expenditure negatively affects economic growth.